Modelling of the effect of fuel reforming and EGR on the acceptable operating range of an ethanol HCCI engine. (13th April 2007) - Ng, Cathy K.W.; Thomson, Murray J.
Homogeneous Charge Compression Ignition (HCCI) engines have great potential in ultra-low NOx emissions, high efficiency and low particulates. However, HCCI also has a narrow operating range with low power output. We therefore investigated the expansion of the Acceptable Operating Range (AOR) using fuel reforming complemented by Exhaust Gas Recirculation (EGR). The modelled HCCI engine is fuelled with ethanol of equivalence ratio (Φ) of 0.2, 0.4 and 0.5. The AOR must meet both the complete combustion and the maximum NOx limit (10 ppm). It is found that fuel reforming enhances combustion and extends the complete combustion limit to lower initial temperatures, but also increases NOx emissions. Since the NOx limit can be greatly extended by the complementary use of EGR, fuel reforming is not as effective as EGR in widening the operating range at the Φ's studied. Therefore, fuel reforming is most beneficial when used at lower initial temperatures near the ignition limit.